PROFITABILITAS, LEVERAGE, PRIOR OPINION DAN KOMPETENSI AUDITOR PADA OPINI AUDIT GOING CONCERN - Aryantika, Ni Putu Putri; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2015)
Based assumption of going concern opinion used by the auditor to prepare financial statements. Assumption appears if the auditor has a doubt of financial statements. Going concern audit opinion provision may worsen the company likes loss of public confidence even go bankrupt. This study aimed to determine the effect of profitability, leverage, prior opinion and auditor competences on a going concern audit opinion. Analyzed by logistic regression concluded that profitability negatively not influence on a going concern audit opinion, leverage and prior opinion influence on a going concern audit opinion and auditor competences influence on a going concern audit opinion.
Keywords: Financial, Audit Opinion, Going Concern